2021
DOI: 10.1007/s11081-021-09653-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the search directions of a mixed DDM applied on cracks

Abstract: Domain Decomposition Methods (DDM) are a set of numerical techniques that efficiently implement parallel computing for the structural analysis of large domains. This work presents the implementation of mixed DDM for linear elasticity problems along with non-linear problems such as crack propagation. In addition, optimization algorithms have been used to find the optimal parameters of the mixed domain decomposition method. Finally, a strategy is proposed in order to implement the optimization methods to obtain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Within this range, an optimum that minimizes the number of iterations can be found. However, as presented in [34,13], the value depends on the problem type, the applied loads, the boundary conditions and the form of the Robin operator used in the analysis. Therefore, in order to find the Robin operator that guarantees convergence and also minimizes the number of iterations until convergence, an optimization process is performed for the different problems presented.…”
Section: Description Of the Optimization Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Within this range, an optimum that minimizes the number of iterations can be found. However, as presented in [34,13], the value depends on the problem type, the applied loads, the boundary conditions and the form of the Robin operator used in the analysis. Therefore, in order to find the Robin operator that guarantees convergence and also minimizes the number of iterations until convergence, an optimization process is performed for the different problems presented.…”
Section: Description Of the Optimization Processmentioning
confidence: 99%
“…The values of the Robin operator assuring the convergence of the non-intrusive method with Robin conditions can be estimated analytically for simple examples with few degrees of freedom. For industrial/real structures, the range of the values are not easily found directly, so these values are found by iterative methods as presented in [20,13] or by using two scale strategies as shown in [27,15].…”
Section: Description Of the Optimization Processmentioning
confidence: 99%
See 1 more Smart Citation